Customer Directed Advertising and Product Quality - Lola Esteban; Jose M. Hernandez; Jose Luis Moraga-Gonzalez (Tinbergen Institute, 2001)
This paper studies the relationship between three key elements of the marketing mix, namely, price, product, and promotion, in a model where a seller employs informative advertising to launch a new product. We propose a fairly general advertising technology for the study of three promotional strategies—mass, imperfectly targeted, and customer directed advertising (CDA). We find that both the private and the social incentives to use distinct advertising strategies are aligned, and that sales are likely to be promoted through CDA. Compared to mass advertising, with CDA the social planner reduces quantity and downgrades quality whereas the seller sometimes upgrades it. Our model of targeting with endogenous product quality provides some new insights into the way the transition from mass to specialized advertising can affect market outcomes. Quality distortions imply that (i) even if CDA increases the market price, the degree of market power need not increase and (ii) CDA may yield a welfare loss even if it leads to a lower market price.
Keywords: L12; L15; M37; 330; customer directed advertising; mass advertising; monopoly; quality; targeted advertising; Werbung; Produktqualität; Theorie